Bioconversion of Keratin Wastes Using Keratinolytic Microorganisms to Generate Value-Added Products - Anbesaw, Muhammed Seid (International Journal of Biomaterials, 2022)
The management of keratinous wastes generated from different industries is becoming a major concern across the world. In each year, more than a billion tons of keratin waste is released into the environment. Despite some trials that have been performed and utilize this waste into valuable products, still a huge amount of keratin waste from different sources is a less explored biomaterial for making valuable products. This indicates that the huge amount of keratin waste is neither disposed properly nor converted into usable products rather thrown away to the environment that causes environmental pollution. Due to the introduction of this waste associated with different pathogenic organisms into soil and water bodies, human beings and other small and large animals are affected by different diseases. Therefore, there is a need for modern and ecofriendly approaches to dispose and convert this waste into usable products. Hence, the objective of this review is to give a concise overview regarding the degradation of keratin waste by biological approaches using keratinase producing microorganisms. The review also focuses on the practical use of keratinases and the economical importance of bioconverted products of keratinous wastes for different applications. Various researches have been studied about the source, disposal mechanisms, techniques of hydrolysis, potential use, and physical and chemical properties of keratin wastes. However, there is negligible information with regard to the use of keratin wastes as media supplements for the growth of keratinolytic microorganisms and silver retrieval from photographic and used X-ray films. Hence, this review differs from other similar reviews in the literature in that it discusses these neglected concerns.